As economias emergentes e o cenário internacional - Renato Baumann Neves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– One of the basic features of last decade was the formation of groups of emerging economies, as well as the acceptance of their role as important players in the determination of global growth. Recent years have shown, however, a fall in the rate of growth of these economies. In this article we show their relative weight in recent years. It is argued that there should be more proactive external trade policies by these countries as a means to foster their presence in the international scenario. Furthermore, these economies should be prepared to face a future situation of less availability of resources in the international market, at least not in the favorable conditions available in recent years.
Keywords: F14; F42; F44; F62; F63; O19; 330; emerging economies; global scenario; environment to trade; cost or resources; investment; future perspectives; financial transmission